Knowledge about slowing of wound healing among undergraduate dental students - Periasamy, Yashila; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Healing of wounds is one of the most interesting phenomena which characterizes the living organism. A healing of the wound results in the death of the organism. So wound healing is essential for the primary survival mechanism. Healing is a process, not an incident and it refers to the replacement of the damaged tissue by the living tissue to restore the function. Aim: To evaluate the knowledge about slowing of wound healing among undergraduate dental students. Materials and method: 200 undergraduate dental students studying in a dental college in South India were selected by convenient sampling method. They were distributed with questionnaire about slowing of wound healing. Data is collected and statistically analyzed. Based on the questionnaire distributed to students, the result have been calculated by dividing the wound healing into three columns as types, phases and factors of wound healing. Data were collected using a self‐administered questionnaire adapted from several studies addressing various aspects of knowledge about slowing of wound healing. Result: On calculating overall percentage of students about knowledge of wound healing, 67% of students have knowledge about wound healing whereas remaining 33% of students lack knowledge about wound healing. Conclusion: On concluding this research, we come to know that students have more knowledge about wound healing. The students who lack knowledge about wound healing should get more attention to it and gain more knowledge about it and will be very useful for their clinical practices.